The COVID-19 Pandemic and Community’s New Habits - Roslinawati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
COVID-19 or coronavirus disease is transmitted from human to human and its spread is getting wider along with human mobility. The wider spread has made various countries implement various policies to stop the spread of the virus. This study aims to determine the impact of the COVID-19 pandemic and the community’s new habits. This study was conducted in Palu City. It used a qualitative approach. The instrument of the study was the researcher with the help of interview guides. The data analysis consisted of data reduction, data presentation, and conclusion drawing. The results of this study showed that COVID-19 has had a major impact on human life and even created new habits in the community